The differential impact of four tropical species of root-knot nematodes (Meloidogyne spp.) on biofortified cassava - Oyetunde, A.K.; Afolami, S.; Kulakow, Peter A.; Coyne, D. (Brill, 2022)
Cassava plays an important food security role in Africa. Although a hardy crop in general, average yields are low, while traditional cultivars tend to be low in nutrients and vitamins. Substantial efforts have therefore been made to improve the nutritional quality of cassava through the development of biofortified cultivars. Although root-knot nematodes (RKN) are among the various important constraints affecting production, details on the impact of different species of RKN on cassava productivity are scarce. In this study, six popular cultivars of biofortified cassava were evaluated for their response to M. arenaria, M. enterolobii, M. incognita, M. javanica and a combination of all four species, in pots. All tested cultivars were susceptible to the four Meloidogyne species, but some cultivars showed a tolerance to M. arenaria infection. Galling damage was observed on feeder roots of inoculated plants, with nematode reproduction factors ranging between 2.3 and 9.5. Plant height, stem girth and fresh plant mass were significantly lower for most cultivars by as much as 70% following RKN infection. The highest root galling and damage were observed in plants following inoculation with a combination of the four species. As individual species inoculations, M. incognita and M. javanica were the most damaging, with the least damage observed in plants inoculated with M. arenaria only. These results confirm the pathogenicity of M. arenaria, M. incognita and M. javanica and further illustrate the potential of M. enterolobii to impact cassava production, while combined species infections demonstrate the greater levels of damage that these may cause.